Modern economic regulation: An introduction to theory and practice - Decker, Christopher (New York Cambridge University Press, 2025)
Economic regulation affects us all, shaping how we access essential services such as water, energy and transport, as well as how we communicate with one another in the digital world. Modern Economic Regulation describes the core insights of economic theory on which regulatory policies are based and connects this with evidence of how regulation is applied.